Practical Multiprocessor Scheduling Algorithms for Efficient Parallel Processing - KASAHARA, H; NARITA, S (IEEE transactions on computers, 1984)
MIMD (multiple instruction stream, multiple data stream) parallel processing systems or multiprocessor systems have been employed in a wide variety of computer applications. In order to take advantage of the prospects of parallel processing, an efficient scheduling algorithm must be developed. Such an algorithm must allow the allocation of a set of tasks to the member processors and the determination of the order or sequence of task execution. The present investigation is concerned with the proposal of suitable algorithms, taking into account the Critical Path (CP) /Most Immediate Successors First (MISF) method. This method represents an improved version of the CP-method or HLFET (highest levels first with estimates times) method. Attention is also given to a method which facilitates finding optimum solutions to a large class of problems.